Obtenção de suspensões celulares de bananeira (Musa spp.) e avaliação da estabilidade genética das plantas regeneradas - Lino, Lucymeire Souza Morais (2009)
The objective of the present work was to establish a quick and efficient methodology for callus and somatic embryo induction, establishment of cell suspension, regeneration in plants and study the genetic stability of the regenerants produced. Immature male flowers of triploid banana varieties (Grande naine, Maçã e Terra) were used for the induction of somatic embryos. The somatic embryos formed were transferred to liquid culture medium for the establishment of the cell suspension for each variety. Experiments were carried out in order to adjust the regeneration protocols for the suspensions via somatic embryogenesis using many combinations of BAP and AIA regulators. The regenerated plants were individualized, rooted and acclimatized under greenhouse conditions and further taken to the field. The evaluation of the genetic stability of the plants generated was carried out using agronomical morphological and molecular (microsatellite marker) characteristics. The time for the induction of embryogenesis in bananas can take up from 45 (‘Terra’) to 180 days (‘Grande naine’). For the regeneration of the cell suspension, the Maçã variety presented best results in MS culture medium without addition of growth regulators. For the Grande naine variety, this same medium presented best results for differentiation into embryos, but these were not converted into plants. For the evaluation of the genetic stability, plants analyzed from the three varieties using agronomical, morphological and molecular characteristics did not show any somaclonal variation, some plants of the Terra variety showed epigenetic variation.